2017
DOI: 10.1155/2017/9510212
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Application of Construction and Demolition Waste in Urban Roads

Abstract: e recycling and reuse of waste materials is a topic of global concern and great international interest for those interested in sustainable development and protecting the environment. In recent decades, global production of construction and demolition waste (C&D waste) has signi cantly increased and became a worldwide problem. is research proposes to evaluate the feasibility of using aggregate from recycled C&D waste for urban road embankment applications based on the Sanhuan road construction project in easter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Almost all the construction technologies were outdated, non-efficient, and in many cases unsafe for use [1][2][3]. Becoming open to new technologies and structural materials provided a strong impact for modernization of the entire construction industry, and until nowadays this trend is still being observed [4][5][6][7][8]. Lack of planning and poor economy management resulted in a huge production of waste, both municipal and industrial, which in many cases were deposited without any control [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all the construction technologies were outdated, non-efficient, and in many cases unsafe for use [1][2][3]. Becoming open to new technologies and structural materials provided a strong impact for modernization of the entire construction industry, and until nowadays this trend is still being observed [4][5][6][7][8]. Lack of planning and poor economy management resulted in a huge production of waste, both municipal and industrial, which in many cases were deposited without any control [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Becoming open to new technologies and structural materials provided a strong impact for modernization of the entire construction industry, and until nowadays this trend is still being observed [4][5][6][7][8]. Lack of planning and poor economy management resulted in a huge production of waste, both municipal and industrial, which in many cases were deposited without any control [3][4][5]. The waste deposition became a serious issue, mainly in well-developed regions like Warsaw or Silesia, where the amount of by-products was rapidly increasing.…”
Section: Introductionmentioning
confidence: 99%
“…For AK0+980, t 0 , t 1 , and t 2 were set at 90, 170, and 250 days, respectively, with the respective S 0 , S 1 , and S 2 being 18.1, 22.4, and 23.2 mm. Using Equations (8) and (9) and with α' = 5.83675 and β' = 0.159599, α' and β' were substituted into Equation (10) and the three-point hyperbolic model for AK0+980 determined as:…”
Section: Settlement Prediction Resultsmentioning
confidence: 99%
“…For example, it was found that CDW could be used as the raw material for the production of recycled aggregate concrete (RAC) for road embankments, subgrades, and foundations [4][5][6][7][8]. Li et al [9] found that after a relatively simple treatment, CDW had high strength and was suitable for urban road embankments; it had an unconfined compressive strength under optimal moisture content from 0.85 to 0.62 MPa, with a mean value of 0.74 MPa, an average CBR value of at least 34.7%, an average embankment deflection of 0.66 mm, and a resilient modulus of 162.7 MPa-all of which met the relevant specifications.…”
Section: Introductionmentioning
confidence: 99%
“…protective barriers). Practical applications and case studies of the successful use of recycled materials for road construction applications have been reported by a number of authors .…”
Section: Introductionmentioning
confidence: 99%